Optimalisasi Implementasi ISAK 35 dalam Organisasi Nonprofit: Upaya Sosialisasi di Panti Asuhan Pelita Harapan - Purba, Sahala; Simanjuntak, Rimky Mandala Putra; Simanjuntak, Reymondo; Andy, Stefanus; Girsang , Chyndi; Sihombing, Vivin (Yumary: Jurnal Pengabdian kepada Masyarakat, 2024)
Purpose: This approach is intended to accelerate the success of orphanages, with an emphasis on developing donor accountability through the preparation of financial documents that comply with ISAK 35 standards. Methodology: The first step of this approach was to interview orphanages regarding the recording mechanism and financial reporting to donors. To explain how the financial recording and reporting system complied with the relevant criteria, we conducted a socialization session. Results: Through the discussion process carried out by the service team, the challenges faced by orphanages in preparing financial reports that meet regulatory requirements have become clear. This is due to a lack of accounting knowledge among orphanage administrators who do not have an educational background in this field. implemented ISAK 35 in its financial reports. As a result, orphanages are motivated to improve their quality by preparing financial reports in accordance with applicable accounting standards, particularly by applying ISAK 35 principles. We hope that this will attract support from new donors. Limitations: The service team focused only on their observations of one orphanage, namely the Pelita Harapan Orphanage. The service team only uses analysis of the orphanage's white board which is displayed every day and The service team manipulates the transaction amount to maintain the privacy of the orphanage Contribution: This service activity at the orphanage shows the orphanage’s high enthusiasm to implement financial reporting in accordance with ISAK 35 in the future. Even though it has succeeded in increasing knowledge and interest in implementing orphanage financial reports according to ISAK 35, there are challenges that need to be overcome, namely, the orphanage's lack of knowledge in the field of accounting to present financial reports.